Observations on the geographic distribution, ecology and conservation status of several phaseolus bean species in Costa Rica - Araya Villalobos, Rodolfo; González Ugalde, W.G.; Camacho Chacon, F; Sánchez Trejos, Maria P.; Debouck, Daniel G. (Springer, 2001)
Interest in bean genetic resources of Central America has resumed because of disease pressures (e.g., web blight, BGMV) and limitations of current bean varieties. As most of the diversity in landraces has been explored, focus is now on the exploration of wild forms of the primary gene pool and wild species of the secondary gene pool. A germplasm collection was carried out in the field and resulted in the collection of 29 wild populations for six Phaseolus species; it complemented field work done in 1987. Nine more populations were found for P. costaricensis, 10 for wild P. lunatus, one for P. oligospermus, one for P. tuerckheimii, four for wild P. vulgaris and four for P. xanthotrichus. Ninety-three herbarium voucher specimens were collected for 19 populations of the six species (deposited at CR). These results confirm the presence of wild P. vulgaris on both slopes of the central valley of Costa Rica, namely in the life zones bh-MB and bmh-P, and of P. costaricensis in the life zone bmh-MB. These life zones of limited range in Costa Rica have been heavily modified, thus fully justifying the germplasm collection for ex situ conservation. For both species the range of distribution in Costa Rica has been almost completely sampled. The life characteristics of each species that are relevant for their conservation in situ are briefly reviewed. Distribution ranges of each wild bean species are compared with the present extension of national parks, protected areas and fauna/flora sanctuaries, and suggestions for expanding such protected areas are made.